Formulation and characterization of levofloxacin-loaded biodegradable nanoparticles - Gevariya, Hitesh B; Gami, Suresh; Patel, Nitin (Asian Journal of Pharmaceutics (AJP), 2014)
Effective management of various ocular infective diseases using levofloxacin eye drops remains challenging owing to poor ocular drug bioavailability. Hence, this study aimed to develop and evaluate nanosphere colloidal suspension-containing levofloxacin as potential ophthalmic drug delivery system.The levofloxacin-loaded chitosan nanoparticles were prepared by ionic gelation of chitosan with tripolyphosphate anions.The nanoparticles were characterized by scanning electron microscopy, zeta potential analyzer, differential scanning calorimetry, and fourier transform infrared spectroscopy. All the prepared formulations resulted in nano-range size particles (317–501 nm) and displayed spherical smooth morphology with zeta potential (+37.2 to +43.5 mV).The encapsulation efficiency and loading capacity were 65–83% and 15–25%, respectively. The levofloxacin-loaded chitosan nanoparticles displayed more crystallinity than levofloxacin. The in vitro diffusion profile of levofloxacin from the nanoparticles showed a sustained release of the drug over a period of 20 h. Kinetic release profiles of levofloxacin from nanoparticles appeared to fit best with Higuchi model with zero order and the non-Fickian diffusion was superior phenomenon. Thus, the results suggest that levofloxacin-loaded chitosan nanoparticle suspension appears to be promising enough for effective management of ocular infections.